Voxel-based meta-analysis of regional white-matter volume differences in autism spectrum disorder versus healthy controls - Radua, J.; Via, E.; Catani, M.; Mataix-Cols, D. (Psychological medicine, 2011)
We conducted a meta-analysis of voxel-based morphometry (VBM) studies in autism spectrum disorder (ASD) to clarify the changes in regional white-matter volume underpinning this condition, and generated an online database to facilitate replication and further analyses by other researchers. PubMed, ScienceDirect, Web of Knowledge and Scopus databases were searched between 2002 (the date of the first white-matter VBM study in ASD) and 2010. Manual searches were also conducted. Authors were contacted to obtain additional data. Coordinates were extracted from clusters of significant white-matter difference between patients and controls. A new template for white matter was created for the signed differential mapping (SDM) meta-analytic method. A diffusion tensor imaging (DTI)-derived atlas was used to optimally localize the changes in white-matter volume. Thirteen datasets comprising 246 patients with ASD and 237 healthy controls met inclusion criteria. No between-group differences were found in global white-matter volumes. ASD patients showed increases of white-matter volume in the right arcuate fasciculus and also in the left inferior fronto-occipital and uncinate fasciculi. These findings remained unchanged in quartile and jackknife sensitivity analyses and also in subgroup analyses (pediatric versus adult samples). Patients with ASD display increases of white-matter volume in tracts known to be important for language and social cognition. Whether the results apply to individuals with lower IQ or younger age and whether there are meaningful neurobiological differences between the subtypes of ASD remain to be investigated.